2017
DOI: 10.15640/ijhs.v5n2a3
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels among Automobile Mechanics in a Megacity, Lagos, Nigeria

Abstract: This study assessed blood lead and Packed Cell Volume (PCV) levels among automobile mechanics in Agidingbi, Ikeja Local Government Area of Lagos. A cross-sectional study was conducted among 37 consented automobile mechanics at a mechanic village in the study setting. Interviews were conducted using a semi-structured questionnaire while blood samples were collected through antecubital fossa. Respondents' mean age was 29 ± 11 years, 64.9% were single while 37.8% were operating as a master of the facility. Some 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In providing their services, these workers carry out tasks like draining fuel or handling dangerous substances that regularly expose them to dust, lead, used auto lubricants, exhaust fumes, or petroleum products (Adejumo et al, 2017;Ndugboe et al, 2014). Several studies among car repair workers demonstrated that the exposure to these hazardous substances was associated with an increased prevalence of health problems, such as cardiovascular, urinary, brain, respiratory, and skin diseases (Adejumo et al, 2017;Ndugboe et al, 2014). Many studies have shown that personal protective equipment (PPE) can protect workers against occupational health problems (Elewon, 2018;Johnson & Motilewa, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In providing their services, these workers carry out tasks like draining fuel or handling dangerous substances that regularly expose them to dust, lead, used auto lubricants, exhaust fumes, or petroleum products (Adejumo et al, 2017;Ndugboe et al, 2014). Several studies among car repair workers demonstrated that the exposure to these hazardous substances was associated with an increased prevalence of health problems, such as cardiovascular, urinary, brain, respiratory, and skin diseases (Adejumo et al, 2017;Ndugboe et al, 2014). Many studies have shown that personal protective equipment (PPE) can protect workers against occupational health problems (Elewon, 2018;Johnson & Motilewa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The use of PPE is not very wide spread among informal automobile artisans in Nigeria. For example, Adejumo et al (2017) reported that 91.9% of the automobile mechanics in a Lagos metropolis did not use PPE while carrying out repairs. Likewise, Ojo et al (2017) reported that only 3% of the car painting workshops in Ile-Ife possessed a respirator with a filter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have established a high prevalence of injuries and illnesses, such as burns, bruises, crushed digits [13], cuts, hand dermatitis, and low back pain [14], in this population [13][14][15][16]. A few studies have evaluated the impact of PWC and worker's health [13][14][15][16][17]; however, these studies did not indicate which of the various PWCs has the largest negative impact on worker's health. Moreover, there has been no evaluation of whether different components of PWC have a similar effect on both illnesses and injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been found to be responsible for these health problems which include exposure to lead46 ; manual lifting of automobile components parts, and awkward postures commonly adopted at work47 ; non compliance and non-usage of personal protective equipment48 ; working for long hours From the foregoing, it is evident that the informal workers earn their livelihood under dangerous and insecure conditions because jobs created under this sector often failed to meet the criteria of decent work. One may argue that the decent work deficit in the informal sector mirrors the state of OHS in Nigeria which some scholars refer to as poor because of under…”
mentioning
confidence: 99%